Humble Leadership, Psychological Safety, Knowledge Sharing, and Follower Creativity: A Cross-Level Investigation - Wang, Yanfei; Liu, Jieqiong; Zhu, Yu (Frontiers in Psychology, 2018)
The leadership literature has provided growing evidence regarding the power of leadership in facilitating follower creativity. Despite these advances, a noticeable omission in this body of research is humble leadership. The study extends previous research by developing a cross-level moderated mediation model and examining the roles that psychological safety and knowledge sharing may play in the relationship between humble leadership and follower creativity. Using a time-lagged data of 328 team members nested within 106 teams, the results show that: (a) psychological safety mediates the relationship between humble leadership and follower creativity; (b) knowledge sharing moderates the relationship between psychological safety and follower creativity; and (c) the indirect influence of humble leadership on follower creativity through psychological safety is stronger when knowledge sharing is high.